Meta-analysis of selected toxicity endpoints of CDK4/6 inhibitors: Palbociclib and ribociclib. (October 2017) - Costa, R.; Costa, R.B.; Talamantes, Sarah M.; Helenowski, Irene; Peterson, Jonna; Kaplan, Jason; Carneiro, B.A.; Giles, Francis J.; Gradishar, W.J.
Abstract: Purpose: Cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitors such as palbociclib and ribociclib are associated with distinct adverse effects (AEs) compared to other targeted therapies. This meta-analysis of clinical trials summarizes these agents' toxicity profile. Methods: A librarian-guided literature search was conducted in March of 2017. The trials needed to have at least one of the study arms consisting of palbociclib or ribociclib monotherapy at currently FDA approved dose regimens. Heterogeneity across studies was analyzed using I 2 statistics. Data were analyzed using random effects meta-analysis for absolute risks. Results: Seven randomized trials and 1, 332 patients were included in our meta-analysis. There was evidence of significant heterogeneity between studies for serious AEs but not for death. The pooled absolute risk (AR) for all-causality serious AEs and treatment-related death were 16% and 0%, respectively. Patients treated with CDK 4/6 inhibitors had an AR of grade 3/4 neutropenia of 61%; neutropenic fever and infections were rare (1% and 3%, respectively). Grade 3/4 nausea, vomiting, and rash were rare. There was no significant correlation between age of patients at study entry and the risk of grade 3/4 neutropenia. Conclusion: Treatment with CDK 4/6 inhibitors is well tolerated and associated with a low risk of treatment-related deaths. There is an increased AR of grade 3/4 neutropenia but a low AR of associated infections. Highlights: Treatment with CDK 4/6 inhibitors is well tolerated. There is increased absolute risk of grade 3–4 neutropenia. Risk of febrile neutropenia is not increased. Treatment-related death is rare.